Micromorphology analysis of specific 3-D surface texture of silver chiral nanoflower sculptured structures - Ţălu, Ştefan; Bramowicz, Miroslaw; Kulesza, Slawomir; Ghaderi, Atefeh; Solaymani, Shahram; Savaloni, Hadi; Babaei, Reza (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
[Display omitted] •We characterized 3-D surface texture of silver chiral nano-flowers with 3-, 4- and 5-fold symmetry.•We prepared thin films by means of oblique angle deposition method.•We determined the Areal Autocorrelation Function (AACF) and pseudo-topothesy K.•We determined the statistical and fractal surface properties of samples. This study presents research into the three-dimensional (3-D) surface texture of silver chiral nanoflowers with three-, four- and five-folds spatial symmetry, which were produced using oblique angle deposition method with rotating sample holder. X-ray diffraction (XRD), atomic force microscopy (AFM), and field-emission scanning electron microscopy (FESEM) measurements were carried out in order to study 3-D morphology and structure of the samples at the nanoscale. Obtained results were found to provide an insight into important relationships between the structure of prepared nanoflowers and their properties. Results presented in the paper proved the usefulness of the method for preparation of high-quality, sculptured 3-D nanostructures with pre-designed shapes (with narrower and longer petals) and desired porosity. Specific structure, shape, and length scale of the 3-D deposits can be then verified in simulations for quick characterization of the samples. This analysis helps to understand their functional role in the test surface, in order to evaluate the relation among the 3-D microtextured surface.